Influence of different morphology of three-dimensional CuxO with mixed facets modified air–cathodes on microbial fuel cell. (November 2015) - Liu, Ziqi; Li, Kexun; Zhang, Xi; Ge, Baochao; Pu, Liangtao
Highlights: The maximum power density was increased up to 77% compared to bare AC cathode. Morphology control of Cu x O was firstly studied as air cathode catalyst in MFC. The Crystallization conditions of Cu x O affect the performance of MFC significantly. Surfactants changed the Cu x O crystallization and composition in electrodeposition. Micropores providing active site facilitate the ORR. Abstract: Three kinds of three-dimensional (3D) Cu x O catalysts were prepared to modify activated carbon air–cathode using a facile electrochemical method with addition of surfactants. The maximum power density of MFC using SC-Cu air cathode (added sodium citrate into the electrolyte solution in electrodeposition process) was 1550 ± 47 mW m −2, almost 77% higher than AC cathode. Specifically, the charge transfer resistance significantly decreased by 89% from 9.3980 Ω to 1.0640 Ω compared to the control. Lumphy and mutually embedded filmy sheet structure were observed in SEM, which provided sufficient active sites for oxygen adsorption and diffusion. In XRD and TEM result, Cu x O with mixed facets showed special structure which had a better performance. Crystallization condition of electrodeposited materials played a significant role in their nature electrochemical properties, morphology controlled by surfactant of Cu x O exhibited high properties on the air–cathode MFC.